Backpacking culture and mobilities: Independent and nomadic travel - Martins, Márcio Ribeiro (2018)
Over the last 40 years significant changes have taken place in the world with impact in the tourism industry. The technological development, the emergence and spread of innovations in telecommunications, transports, accommodations, and marketing, and the (re)emergence of public health threats as COVID-19 and the manifestation of natural and anthropic hazards, introduced profound transformations into the way we travel. Backpacker tourism in not an exception.